A new genus of oonopid spiders from Myanmar (Araneae, Oonopidae) - Yanfeng Tong; Haifeng Chen; Sijia Liu; Shuqiang Li (ZooKeys, 2018)
A new genus, Kachinia Tong & Li, gen. n., including two new species, K. putao Tong & Li, sp. n., and K. mahmolae Tong & Li, sp. n., is described from Myanmar. The new genus belonging to the subfamily Oonopinae Simon, 1890, currently is the only member of the Brignolia-Opopaea clade with leg spines.